Advanced imaging technology applications in cytology. Issue 1 (12th February 2018) - Pantanowitz, Liron; Preffer, Frederic; Wilbur, David C.
Abstract : Novel techniques have been developed to image cells at cellular and subcellular levels. They allow images to be analyzed with ultra‐high resolution, in 2D and/or 3D. Several of these tools have been tested on cytology specimens demonstrating emerging applications that are likely to change the field of cytopathology. This review covers several of these advanced imaging methods. The use of optical coherence tomography to perform optical biopsies during endoscopic ultrasound procedures or visualize cells within effusion samples is discussed. The potential for quantitative phase microscopy to accurately screen Pap test slides or resolve indeterminate diagnoses in urine cytology is reviewed. The article also examines the application of 3D cytology using LuCED for lung cancer detection in sputum samples and the feasibility of imaging flow and mass cytometry to measure multiple biomarkers at the single cell level. Although these novel technologies have great potential, further research is necessary to validate their routine use in cytopathology practice.